Association of Physician Assistant Programs [Membership List, November 1973] - Association of Physician Assistant Programs (1973)
Association of Physician Assistant Programs membership list containing the names of 26 educational programs and representative that was mailed prior to the November 1973 meeting held in conjunction with the AAMC in Washington, DC.